Recent advances in the management and implementation of care for familial hypercholesterolaemia - Nick S.R. Lan; Archna Bajaj; Gerald F. Watts; Marina Cuchel (Elsevier, 2023)
Familial hypercholesterolaemia (FH) is a common autosomal semi-dominant and highly penetrant disorder of the low-density lipoprotein (LDL) receptor pathway, characterised by lifelong elevated levels of low-density lipoprotein cholesterol (LDL-C) and increased risk of atherosclerotic cardiovascular disease (ASCVD). However, many patients with FH are not diagnosed and do not attain recommended LDL-C goals despite maximally tolerated doses of potent statin and ezetimibe. Over the past decade, several cholesterol-lowering therapies such as those targeting proprotein convertase subtilisin/kexin type 9 (PCSK9) or angiopoietin-like 3 (ANGPTL3) with monoclonal antibody or ribonucleic acid (RNA) approaches have been developed that promise to close the treatment gap. The availability of new therapies with complementary modes of action of lipid metabolism has enabled many patients with FH to attain guideline-recommended LDL-C goals. Emerging therapies for FH include liver-directed gene transfer of the LDLR, vaccines targeting key proteins involved in cholesterol metabolism, and CRISPR-based gene editing of PCSK9 and ANGPTL3, but further clinical trials are required. In this review, current and emerging treatment strategies for lowering LDL-C, and ASCVD risk-stratification, as well as implementation strategies for the care of patients with FH are reviewed.